Investigation of in vitro and in vivo therapeutic activity of Tarantula cubensis extract (Theranekron®) on Leishmania major - Elif Akyol; Zübeyda Akın Polat (Journal of Vector Borne Diseases)
Background & objectives: Cutaneous leishmaniasis (CL) is a vector-borne parasitic disease caused by several species of the protozoan parasite Leishmania. The need for new anti-leishmanial drugs for the treatment of CL is complicated by factors such as high cost, toxicity, potential for resistance and limited long-term use of existing anti-leishmanial drugs. The aim of this study was to investigate the therapeutic effect of Tarantula cubensis alcoholic extract (TCE), which has been shown to have wound-healing, anti-inflammatory, regenerative, resolving and epithelialising effects, on Leishmania major promastigotes in vitro and in vivo in an experimental mouse model of CL. Methods: The effect of TCE on L. major promastigotes in vitro was investigated after determining non-cytotoxic concentrations of TCE using the XTT method. To establish a CL model, L. major amastigotes were injected into the paws of BALB/c mice. Lesion size and histopathological evaluation were used to assess the effect of treatment. Results: TCE was found to be effective against L. major promastigotes at 24 h and 48 h at concentrations 250 μg/ mL, 125 μg/mL and 62.5 μg/mL (P<0.05). TCE was found to be more effective than meglumine antimonate in treating CL in the experimentally induced CL model in BALB/c mice. Interpretation & conclusion: The results suggest that TCE holds promising potential as a therapeutic agent for the treatment of CL. However, further extensive investigations are required to substantiate and expand our understanding in this area.